Ontogeny of anti-human immunodeficiency virus (HIV) antibody production in HIV-1-infected infants. - Pollack, H (1993)
The early serologic response of infants to infection with human immunodeficiency virus type 1 (HIV-1) is normally obscured by the presence of transplacentally acquired maternal HIV antibody. By measuring HIV antibody produced in vitro by lymphocytes isolated from peripheral blood of infants and children of HIV-1-infected mothers, we have been able to study the natural acquisition of humoral immunity to perinatal HIV-1 infection. One hundred ninety-seven infants of HIV-1-infected women were studied prospectively and longitudinally from birth. In the neonatal period, infected infants produced only small amounts of HIV-specific IgG antibodies to a restricted number of antigens. The amount of immunoglobulin to HIV-1 and the number of HIV-1 antigens recognized increased with age. After 6 months of life 85% of infected infants made detectable antibody to two or more viral proteins. Antibody to gp160 appeared first and was the most frequently found at all ages, followed by antibody to the envelope proteins gp120 and gp41. The amount of HIV antibody produced correlated positively with the percentage of CD4+ T lymphocytes in peripheral blood. This assay provides a method of studying the immunogenicity of vaccines against HIV-1 in HIV-1-infected infants and of assessing the effect of early therapeutic interventions on the humoral response to HIV-1.